Zinc oxide tetrapods as novel field emitters with low turn-on voltage - Filippo Giubileo; Enver Faella; Arun Kumar; Sebastiano De Stefano; Loredana Viscardi; Kimberly Intonti; Ofelia Durante; Aniello Pelella; Adolfo Mazzotti; Nadia Martucciello; Eugeniy Beliayev; Yogendra Kumar Mishra; et al. (Nano Express)
We investigate the field emission properties of tetrapod-shaped zinc oxide (ZnO) micro and nanostructures prepared using a flame transport synthesis approach. Using a piezo-driven metallic tip as an anode, we performed a local characterization from the apex of a tetrapod arm, where the effective emitting area was limited below 1 μm ^2 . This configuration allows extremely low turn-on voltages, of 7 V, and a field enhancement factor of 70 at an anode-cathode distance of 600 nm. The experimental data were analyzed using the Fowler–Nordheim model, evidencing a non-monotonous dependence of the turn-on field and the field enhancement factor on the cathode-anode separation distance in the range of 100–900 nm. The ZnO tetrapods demonstrated good current stability, highlighting their potential for high-performance, low-consumption electron-emitting devices with very low turn-on voltage.